Use of Semiautomated Machinery in the Productivity of the SENA Centro de Manufactura en Textil y Cuero, Bogotá - Pardo Gutiérrez, Miguel Ángel
Professional in Production Engineering and Master's in Industrial Engineering with an emphasis on organizational management from the Francisco José de Caldas District University in Bogotá. With over 20 years of experience in the private sector, they have held management positions in productivity, plant management, and production direction in companies such as Pat Primo, Hilacol SA, Pacific Cotton, and Andina Team. Currently, they serve as an Instructor in the Research, Technological Development, and Innovation System (SENNOVA), a part-time university lecturer, and consultant for firms like Quality Protec and HGJS Consultants. Their focus lies in areas such as technological capacity management and data analytics in the textile industry.